x/(2x+3)=(x-1)/(2x)

Simple and best practice solution for x/(2x+3)=(x-1)/(2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x/(2x+3)=(x-1)/(2x) equation:


D( x )

2*x+3 = 0

2*x = 0

2*x+3 = 0

2*x+3 = 0

2*x+3 = 0 // - 3

2*x = -3 // : 2

x = -3/2

2*x = 0

2*x = 0

2*x = 0 // : 2

x = 0

x in (-oo:-3/2) U (-3/2:0) U (0:+oo)

x/(2*x+3) = (x-1)/(2*x) // - (x-1)/(2*x)

x/(2*x+3)-((x-1)/(2*x)) = 0

x/(2*x+3)+(-1*(x-1))/(2*x) = 0

(2*x*x)/(2*x*(2*x+3))+(-1*(x-1)*(2*x+3))/(2*x*(2*x+3)) = 0

2*x*x-1*(x-1)*(2*x+3) = 0

3-x = 0

(3-x)/(2*x*(2*x+3)) = 0

(3-x)/(2*x*(2*x+3)) = 0 // * 2*x*(2*x+3)

3-x = 0

3-x = 0 // - 3

-x = -3 // * -1

x = 3

x = 3

See similar equations:

| 98=7(x+8) | | 8a=0.32 | | 17-2x-7=2-2x | | 6-6x=6x-9x-9 | | x(x-1)=x(x+1) | | 60-8x=8x | | 11y-6y-13=55.90 | | 6-24x+36y=0 | | -25+3x=-2x | | 11x-9-5=10x-4+3x | | 4x+5x-42=70-5x | | 15x=4/10 | | (x-5)+17=-3 | | 2tsp=XmL | | 38-4x=12+9x | | 42-n=28 | | -11=3+7x | | b-3+4b=-7+4b | | 3/5+2x=2/5 | | 4(x+18)=-2(x-6) | | -11X+6Y=-13 | | 2w-15w-18=-83 | | 13y-10y=9 | | (2xy-y)(2xy-y)= | | 46q-34=54q-82 | | 1/4x+3=17 | | (n/8)-3=-11 | | -7(1+7r)-6=379 | | s^2+8s-9=0 | | 125m-75m+43875=46125-175m | | 2x+3(-8)=0 | | 15x-2.4x=0.6+7.6x |

Equations solver categories